2021
DOI: 10.1063/5.0052229
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of single- and two-phase flow in porous media with a bifurcated fracture

Abstract: Considering that fractures arising from fracturing systems have bifurcation characteristics, mathematical models for single- and two-phase flow in porous media with a bifurcated fracture (BFPM) were established. The phase-field method was adopted to trace the oil–water interface, and the influence of fracture morphology, boundary conditions, gravity, and wettability on imbibition in BFPM was discussed. The results are as follows: (1) during single-phase flow in BFPM, the velocity in the bifurcated fracture was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…16− 18 Many researchers assumed that fractures resembled a forked symmetric fracture network through referral to fracture fractal theory and to characterize the complex bifurcated fracture network structure based on simple mathematical iteration. 10,19,20 However, the above research was constructed on a static fractal dimension, which was inconsistent with the actual situation. Porosity varied during the shale gas production process under the influence of various factors, 21 indicating that the pore's heterogeneity, including pore size, also differed and was not constant; therefore, the fractal dimension characterizing the pore's heterogeneity should reflect change.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…16− 18 Many researchers assumed that fractures resembled a forked symmetric fracture network through referral to fracture fractal theory and to characterize the complex bifurcated fracture network structure based on simple mathematical iteration. 10,19,20 However, the above research was constructed on a static fractal dimension, which was inconsistent with the actual situation. Porosity varied during the shale gas production process under the influence of various factors, 21 indicating that the pore's heterogeneity, including pore size, also differed and was not constant; therefore, the fractal dimension characterizing the pore's heterogeneity should reflect change.…”
Section: Introductionmentioning
confidence: 92%
“…Shale being a typical dual-porosity structure, researchers have amalgamated gas flow, deformation, matrix-fracture interaction, and heat transference to develop a dual-porosity permeability model in order to investigate the interaction between the matrix-fracture microstructure and macroscopic behavior . However, none of the above studies considered the complex features of the fracture bifurcation structure, which over time has revealed that fractures in shale’s low permeability reservoirs possess bifurcation characteristics similar to a tree network pattern. Many researchers assumed that fractures resembled a forked symmetric fracture network through referral to fracture fractal theory and to characterize the complex bifurcated fracture network structure based on simple mathematical iteration. ,, However, the above research was constructed on a static fractal dimension, which was inconsistent with the actual situation. Porosity varied during the shale gas production process under the influence of various factors, indicating that the pore’s heterogeneity, including pore size, also differed and was not constant; therefore, the fractal dimension characterizing the pore’s heterogeneity should reflect change.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the fluid inlet, when the shear displacement is 0 (the contact area is minimal), the pressure drops in a "wave" shape (Zhu et al 2021). With the increase of shear displacement (the contact area after the increase of the shear displacement is larger than the contact area when the shear displacement is 0 mm), the flow velocity near the contact parts change greatly, resulting in the change of the pressure (Fig.…”
Section: Mesoscopic Fluid Flow In Fracture At Different Shear Displac...mentioning
confidence: 99%
“…Researchers employed both physical and numerical simulation methodologies to assess the influence of distinct fracture–matrix systems on the development of low-permeability oil and gas resources. The utilization of indoor physical simulation methods offers a more faithful reproduction of actual reservoir conditions and oil displacement processes. This facilitates an analysis of the displacement phenomena and oil displacement mechanisms.…”
Section: Introductionmentioning
confidence: 99%